Control of Listeria Monocytogenes in ready-to-eat meats using cetyl pyridinium chloride - Singh, M.; Thippareddi, H.; Phebus, Randall K.; Marsden, James L.; Kastner, Curtis L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Cetyl Pyridinium Chloride (CPC) spray using variable application temperatures, pressures, and times was evaluated for its effectiveness in reducing Listeria monocytogenes inoculated on the surfaces of commercial frankfurters and Polish sausage. Frankfurters and Polish sausage were inoculated with a five-strain cocktail of L. monocytogenes (101M, 109, 108M, serotype 4c ATCC, and serotype 3 ATCC) and subjected to no treatment, CPC treatment, and CPC followed by water treatment. CPC (1%) was applied to the frankfurters and Polish sausage by spraying in a cabinet using all combinations of 77, 104, and 131°F spray temperatures; 20, 25, and 35 psi spray pressures; and 30, 40, and 60 second times of exposure. No individual effect (P>0.05) of any particular application temperature, pressure, or time on the reduction of L. monocytogenes was observed. Hardness and color of the product was not affected when treated with 1% CPC. From initial inoculum levels of 8.20 log colony forming units (CFU)/gram, 1% CPC reduced L. monocytogenes by 1.19 to 2.39 log CFU/gram.
Keywords: Beef; Listeria monocytogenes; Cetyl pyridinium chloride